Binding affinity of aniline-substituted dodecaborates to cyclodextrins. Issue 14 (26th January 2022) - Marei, Tarek; Al-Joumhawy, Mahmoud K.; Alnajjar, Mohammad A.; Nau, Werner M.; Assaf, Khaleel I.; Gabel, Detlef
Abstract : Structure–activity relationships of dodecaborate-substituted nitroanilines as hosts in cyclodextrins have been elucidated. Abstract : A new set of hybrid guest molecules bearing organic and inorganic residues have been studied for their recognition by cyclodextrins in aqueous solution. The guest molecules consist of nitroanilines linked through their amino group to the dodecahydrido- closo -dodecaborate cluster B12 H12 2−, which serves as an anchor group. They show sizable affinity to cyclodextrins, and unexpected photophysical properties, with a very strong and low-energy charge-transfer band. The dodecaborate cluster increases the p K a of the anilines by 5.0 to 5.7 pH units, and the deprotonated forms of the o - and p -nitroaniline derivatives show strong charge transfer absorption bands in the visible part of the spectrum.